Celulosic Nanofiber Kenaf Bast Using Supercritical Co2 Technique As Reinforcement In Nanocomposite For Premium Packaging Applications - Mohd Saad, Nurul `Atiqah (2021)
This study investigates the characteristic functional properties of cellulose nanofibers (CNF) from kenaf fiber extracted via a total chlorine-free (TCF) bleaching method followed by an eco-friendly supercritical carbon dioxide (SC-CO2) treatment process.